2010
DOI: 10.1186/1756-0500-3-333
|View full text |Cite
|
Sign up to set email alerts
|

Morphological analysis of the sheathed flagellum of Brucella melitensis

Abstract: BackgroundIt was recently shown that B. melitensis is flagellated. However, the flagellar structure remains poorly described.FindingsWe analyzed the structure of the polar sheathed flagellum of B. melitensis by TEM analysis and demonstrated that the Ryu staining is a good method to quickly visualize the flagellum by optical microscopy. The TEM analysis demonstrated that an extension of the outer membrane surrounds a filament ending by a club-like structure. The ΔftcR, ΔfliF, ΔflgE and ΔfliC flagellar mutants s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
36
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 51 publications
0
36
1
Order By: Relevance
“…Bacteria were grown in rich medium at 37 uC to OD 600 0.25 as described previously (Ferooz & Letesson, 2010). The bacteria were centrifuged at 1000 r.p.m.…”
Section: Detection Of Flge and Flic Proteins By Western Blot Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Bacteria were grown in rich medium at 37 uC to OD 600 0.25 as described previously (Ferooz & Letesson, 2010). The bacteria were centrifuged at 1000 r.p.m.…”
Section: Detection Of Flge and Flic Proteins By Western Blot Analysismentioning
confidence: 99%
“…For a long time, they were considered as being unflagellated. However, a sheathed flagellum has recently been discovered in Brucella melitensis and flagellar mutants are found to be impaired for infection in vivo (Ferooz & Letesson, 2010;Fretin et al, 2005;Zygmunt et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This intracellular pathogen belongs to the a-2 subgroup of proteobacteria, including the genera Agrobacterium, Rhizobium and Rickettsia, which also live in close association with a eukaryotic host (Batut et al, 2004;Ugalde, 1999). For a long time, brucella was considered to be non-flagellated, but recent studies have demonstrated that B. melitensis produces a polar sheathed flagellum during the beginning of the exponential growth phase in rich medium and that the flagellar genes are required for the establishment of in vivo infection in mice and goats (Ferooz & Letesson, 2010;Fretin et al, 2005;Letesson et al, 2002;Zygmunt et al, 2006).The structure of the bacterial flagellum is classically divided into three main components: the MS-ring in the basal body, the hook and the filament encoded by the fliF, flgE and fliC genes, respectively. The molecular processes involved in assembly of the bacterial flagellum have been extensively studied in the enterobacteria Escherichia coli and Salmonella enterica serovar Typhimurium (Macnab, 1996).…”
mentioning
confidence: 99%
“…B. melitensis FlbT shares 31 % sequence identity with FlbT of C. crescentus and 58 % sequence identity with FlbT of S. meliloti. To investigate the potential regulatory function of B. melitensis FlbT, we generated an flbT deletion mutant.Since the flagellum of B. melitensis is produced only during early exponential phase in rich liquid medium (Ferooz & Letesson, 2010;Fretin et al, 2005), B. melitensis wild-type strain and flbT mutant samples were taken during early exponential phase and a Western blot analysis was performed to detect FliC synthesis (Fig. 2a).…”
mentioning
confidence: 99%